A Rare Complication of Inhaler Use; Open Globe Injury and Blow Out Fracture After the Inhaler Explosion - Yıldırım, Hakan; Canleblebici, Mehmet; Balbaba, Mehmet (My University, 2020)
Open globe injury (OGI) is a serious ophthalmological emergency resulting in loss of vision. Most of these injuries are caused by preventable accidents. Inhalers used in as asthma medication and in some respiratory diseases could contain compressed gas. These inhalers could be exploded by high temperature and cause traumatic injuries. This is the first report of an inhaler explosion causes an OGI with blow out fracture (BOF) and it ends with evisceration. In this article, we present a 58 years old woman with OGI and BOF requiring evisceration as a re-sult of the explosion of an inhaler with containing compressed gas used for her asthma. These inhalers should have warning signs and labels to prevent trauma caused by inhalers. The patients and their relatives should be warned that these drugs may explode and, if possible, these drugs should be replaced with non-explosive forms for preventing possible injuries.
Keywords: Genel ve Dahili Tıp; Göz Hastalıkları